Side effects of fiscal rules: a case of Polish local self‑government - Banaszewska, Monika (Economics and Business Review, 2018)
The trend towards decentralization of government activities has prompted an increased interest in sub-national fiscal rules. The paper investigates an ex ante adaptation to the modified subnational fiscal framework. Using a panel of 2,479 Polish municipalities in the years 2011-2013 the aim is to verify the existence of the side effect of the new debt repayment rule. The empirical results show that local government units for which the new rule would have been more demanding than the former generated higher revenues per capita from asset sales.